PENGARUH KOOPERATIF LEARNING TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP MINAT SISWI KELAS XI DALAM PEMBELAJARAN SENAM LANTAI ROLL BELAKANG - Restu Maulana; Dr. Citra Resita, S.Pd., M.Pd; Asep Suherman, S.Pd., M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Team Games Tournament (TGT)type cooperative learning model on class XI female students interest in learningfloor exercise, especially the back roll movement. The TGT model is a cooperativelearning approach that combines academic activities with elements of games andcompetition, so it is hoped that it can increase students motivation and interest inlearning. This research uses quantitative methods with a quasi-experimentaldesign. The research sample consisted of class XI female students at YosSudarso Karawang High School who were divided into an experimental group anda control group. The research instrument is a learning interest questionnaire andobservation of learning activities. The results of data analysis show that there is asignificant increase in interest in the group using the TGT learning modelcompared to the group using conventional methods. Thus, it can be concludedthat the application of the TGT type cooperative learning model has a positiveeffect on increasing female students interest in learning back roll floor exercises.